Преобразование Бианки катушки Миндинга в E3 - М.А. Чешкова (Труды семинара по геометрии и математическому моделированию, 2022)
The work is devoted to the construction of the Bianchi transform for surfaces of revolution of constant negative Gaussian curvature. The surfaces of revolution of constant negative Gaussian curvature are the Minging top, Minging coil, pseudosphere (Beltrami surface). Constructed Bianchi transform for Minding coil. The surfaces under study are described using elliptic integrals. Using the math package, the Minging coil and its Bianchi transform are built. The surfaces under study are described using elliptic integrals.